Efficacy of Clinical Palpation to Detect Cervical Lymph Node Metastasis of Oropharyngeal Cancer (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: Before excision of the primary tumor in oropharyngealcancer, a decisionmust be made to treat the cervical lymph nodes (LN) or not. The study aimed to assess the role of clinicalpalpation (CP) for preoperative detection of LN metastasis.Methods: Twenty patients withoropharyngeal squamous cell carcinoma (OSCC), managed by excision of theprimary tumor andneck dissection. The histopathological examination results compared to the preoperativeassessment of the nodes by CP.Results: There were 20 patients involved, 11 males and nine females. The mean age was 54.5 years. Twentyneck dissections were performed; there was 14 LN metastasis as proved by histopathological examination.On CP, true positive was 12, false negative was two, true negative was two and false positive was four.Conclusion: Clinical palpation performed preoperatively is highly advised as it has high diagnosticcapabilities to reach a decision to do neck dissection or not.